Pengembangan Rancangan Aplikasi Perhitungan Indikator Pelayanan Rawat Inap Berbasis Komputer di Rumah Sakit Ciamis - Irpan Ali Rahman; Iin Inayah; Lilis Rohayani (Health Information : Jurnal Penelitian, 2020)
The bed information system is a form of management that plays a role in improving the quality of hospitals. The reporting of inpatient performance still has barriers and constraints to overcome these required computer-based tools to facilitate the calculation process. The purpose of this research is to develop the design of computer-based calculation applications. This type of qualitative research with research and development design is in the fifth phase and is at level one. The assessment results from the media experts acquired an average value of 4 including the 'worth' category and material experts get an average rating of 4.27 in the category of 'very decent'. Conclusion that the overall design of the application can be applied. The advice of this research is expected to utilize the information system to facilitate the head of the room as well as the management of the hospital and for researchers then expected to continue on level 2, 3, and 4.